2016
DOI: 10.20448/journal.509/2016.3.3/509.3.98.105
|View full text |Cite
|
Sign up to set email alerts
|

The Students Satisfaction Oriented: Academic Service Improvement Strategy, Department of Aquatic Resources Management, Bogor Agricultural University, Indonesia

Abstract: Higher education institutions must have a strategy change management in the increasingly competitive business environment. A continous performance improvement should be made accordingly. This study was conducted with the case of MSP-IPB, to analyze the priority of academic services improvement which were oriented in student satisfaction. This study used a survey design. Conducted using SERVQUAL instrument with 195 active students of undergraduate program in academic year 2014/2015 as respondents. Principal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…Competencies are technical and non-technical factors such as personality and behavior, soft skills and hard skills that are owned by someone. Based on the opinions of several experts (Adedoyin & Okere, 2017;Bailey, 2003;Barac, et al, 2016;Blunt, 2014;BPKP, 2010;Gambari, Shittu & Taiwo, 2016;Frima & Ghina, 2017;Chen et al, 2017;Levina et al, 2017;Khrulyova & Sakhieva 2017;Mohammed, Joshua & Ahmed, 2018;Omarova et al, 2018;Nyarko, Agbemava, & Bediako, 2016;Sanghi, 2007;Spencer & Spencer, 1993;Tuanakotta, 2011;Widaryanti, Daryanto, & Fauzi, 2016;Zandi & Elwahi, 2016), it was concluded that Auditor Competencies include knowledge, skill, ability, suitability of personal behavior possessed to be able to perform his / her duties with good and objective results.…”
Section: Auditor Competencymentioning
confidence: 99%
“…Competencies are technical and non-technical factors such as personality and behavior, soft skills and hard skills that are owned by someone. Based on the opinions of several experts (Adedoyin & Okere, 2017;Bailey, 2003;Barac, et al, 2016;Blunt, 2014;BPKP, 2010;Gambari, Shittu & Taiwo, 2016;Frima & Ghina, 2017;Chen et al, 2017;Levina et al, 2017;Khrulyova & Sakhieva 2017;Mohammed, Joshua & Ahmed, 2018;Omarova et al, 2018;Nyarko, Agbemava, & Bediako, 2016;Sanghi, 2007;Spencer & Spencer, 1993;Tuanakotta, 2011;Widaryanti, Daryanto, & Fauzi, 2016;Zandi & Elwahi, 2016), it was concluded that Auditor Competencies include knowledge, skill, ability, suitability of personal behavior possessed to be able to perform his / her duties with good and objective results.…”
Section: Auditor Competencymentioning
confidence: 99%
“…An institution which faces rapid changes has the choice of adapting to change or opposing the change. For implementation of change successfully, readiness for change helps to avoid inter personal conflicts and issues of governance in the organization (Armenakis et al, 1993;Garrison et al, 2006;Andersen, 2008;Widaryanti et al, 2016;Yanga and Yenb, 2016). A major challenge in the implementation of change is also felt when a few individuals categorize change as positive or negative.…”
mentioning
confidence: 99%
“…If the SERVQUAL score < 0, meaning that the expectation of service users remain unfulfilled by services provided. This matter also occurs in researches conducted by Voss et al (2007); Kontic (2014) and Widayanti (2016) suggested quality gap value for the whole service quality dimensions scored negative. Besides that, the result of research by Bangun (2013) indicates the whole variable scored negative gap value.…”
Section: Figure-1 Catresian Diagram Of the Survey Resultsmentioning
confidence: 82%
“…If the SERVQUAL score < 0, this means that the services provided have not fulfilled the expectation of service users. This result also occurred in Voss et al (2007); Kontic (2014); Widayanti (2016) which was suggested that the quality gap value in all service quality dimensions scored negative. Moreover research by Bangun (2013) also presented that the overall variables possessed a negative gap value.…”
Section: Gap Servqual Analysismentioning
confidence: 75%